Transarterial chemoembolization vs bland embolization in hepatocellular carcinoma: A meta-analysis of randomized trials - Facciorusso, Antonio (United European Gastroenterol J, 2016)
BACKGROUND: Although transarterial chemoembolization is considered the standard of care for intermediate hepatocellular carcinoma patients, robust data in favor of a clear superiority of chemoembolization (with chemotherapy injection) over bland embolization are lacking. OBJECTIVE: The objective of this article is to systematically analyze the results provided by randomized controlled trials comparing these two treatments in hepatocarcinoma patients. METHODS: A computerized bibliographic search on the main databases was performed. Survival rates assessed at one, two, and three years, objective response, one-year progression-free survival, and severe adverse event rate were analyzed. Comparisons were performed by using the Mantel-Haenszel test in cases of low heterogeneity or DerSimonian and Laird test in cases of high heterogeneity. RESULTS: Six trials with 676 patients were included. No difference in one-year (risk ratio: 0.93, 0.85–1.03, p = 0.16), two-year (risk ratio: 0.88, 0.74–1.06, p = 0.18) and three-year survival (risk ratio: 0.97, 0.74–1.27, p = 0.81) was observed. Objective response and one-year progression-free survival showed no significant difference between the two treatments (p = 0.36 and p = 0.40, respectively). A statistically significant increase in severe toxicity after chemoembolization was found (risk ratio: 1.44, 1.08–1.92, p = 0.01), although this result could be affected by the heterogeneity of techniques adopted. CONCLUSIONS: Our meta-analysis demonstrates a non-superiority of transarterial chemoembolization with respect to bland embolization in hepatocarcinoma patients.